Argo ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN EARNINGS DAN CAPITAL PADA BANK UMUM KONVENSIONAL PERSERO YANG TERDAFTAR DI BANK INDONESIA - Argo Putra Prima (Politeknik Caltex Riau, 2018)
In the world of banking, the soundness of banks is an important element in the survival of a banking institution. Banks can be said to be healthy if they can maintain the security and money of the people stored in the bank, can develop well and be able to contribute meaningfully to the development of social economy. This study aims to determine the level of Health of Conventional Commercial Banks Registered at Bank Indonesia in terms of Earnings dani Capital in the period 2011-2015. The results of earnings calculations indicate that the majority of Conventional Commercial Banks listed at Bank Indonesia obtain ROA values ​​above 1, 25%, and there is an analysis of ROA ratios with the predicate of a fairly healthy bank owned by the State Savings Bank (Persero) in 2014 of 1.12%. Based on Earnings factor or profitability as measured by the ratio of NIM (Net Interest Margin) to Conventional Commercial Banks, the Company as a whole has an NIM on Composite Rating 1 with very healthy information. Analysis of the Bank's Health with Capital factors measured by the ratio of CAR to conventional Conventional Commercial Banks during 2011 - 2015 has a CAR value above 8%. Overall the predicate of banks with CAR ratio is Very Healthy. This shows that BNI, BRI, BTN and Bank Mandiri are able to manage capital very well in accordance with the characteristics, business scale and business complexity of the company and also have a good level of capital adequacy for the fulfillment of their obligations and can overcome the possibility of risk.